Perumusan Persepsi Kenyamanan Termis Pejalan Kaki di Iklim Tropis Lembab dan Membandingkan dengan Rumus untuk Iklim lainnya - Sangkertadi, S; Syafriny, Reny (Forum Geografi, 2012)
This article is about development a regression equation to determine the perception of thermal comfort for pedestrians in the humid tropical climate. Methods used was field studies and questionnaires to 60 samples as respondents in Manado. Each of the respondents was asked to act as pedestrian but walked on a treadmill for 2 minutes 5 five times. They regrouped into two parts, one who walked under open-sky and another group was under the shade of trees. Measurements of climate variables include air temperature, air humidity, radiation temperature, land surface temperature and solar radiation. Measurements to the respondents were their height, weight and skin temperature. By using statistical approach it is obtained a regression equation "Y=- 6.1369 + 0.479 Adu + 0.1143 Ta + 0.0376 Trm + 0.2541 RH + 1.6793 clo". The equation was then validated by comparison with other equations of non-tropical humid climate case. It is found that the empirical regression equations of outdoor thermal comfort developed by means of field studies in a certain climatic conditions could not be applied for a wide range of climate.